European Journal for Education Law and Policy Journal of the European Association for Education Law and Policy. - SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: .)
As of 2002 this journal is no longer published by Springer and has been discontinued.
Keywords: International education; Comparative education; Private international law; Conflict of laws; International law; Comparative law; Public international law; Public International Law; Private International Law, International & Foreign Law, Comparative Law; International and Comparative Education